The interference management and cost analysis perspective of femtocell in 4G network - Shabnam, Farzana; Shemonti, Nazifa M.; Ibnat, Aniqa A.; Chakraborty, Arnoba (© 2016 IEEE., 2018)
This conference paper was published in the IEEE Xplore [ © 2016 IEEE] and the definite version is available at : http://doi.org/10.1109/WIECON-ECE.2016.8009095 The Journal's website is at: http://ieeexplore.ieee.org/document/8009095/